You are on page 1of 15

K 4

A
4.1
4.1.1 a : ` \
.
(1), (2),,a(n), 1, 2, , n,
n .
{n}nN, n (n).
a : ` \

= {(n, an ) : n `} .


.
0.9
0.8
0.7
0.6

10

15

20

:
() , .. n = n2+1:
1 = 12+1=2,
2 = 22+1=5,

10 =102+1=101,

()
, .. 1 =1, 2 =3, n+1 = n+n-1. T:
3 = 2 + 1 =3+1=4,
4 = 3 + 2 =4+3=7,
5 = 4 + 3 =7+4=11,

n .
M n

68

M \ : an M n ` .
H n
M \ : an M n ` .
H n
m,M \ : m an M n ` .
n
M > 0 : | an | M , n ` .
H n (. )
an < an +1 (. an an +1 ) .
H an (. )
an > an +1 (. an an +1 ) .
an () ()
an () .
4.2
2 x0
x0 .
.
,
+. 2

, .
lim n + an .
O 4.2.1 n a \ ,
lim n+ an = a ,
> 0 n0 ` : n > n0 an a < .

:
>0 n0
n n0
(-,+).

69

O 4.2.2 n +,
lim n+ an = + ,
> 0 n0 ( ) ` : n > n0 an > .
:
>0 n0
n n0
n .
800
600
400
200

10

15

20

25

30

O 4.2.3 n -,
lim n+ an = ,
> 0 n0 ( ) ` : n > n0 an < .
:
>0 n0
n n0
n -.

70

10

15

20

25

30

-200
-400
-600
-800

n
.
( ).

n n+
:
> 0 : n0 , n > n0 : an a .

A
40

1.5
1

20

0.5

10
10

20

30

20

30

40

40

-20

-0.5
-1

-40

4.3
4.3.1 .
. an a, an b . =

| a b|
:
2

> 0 n1 ` : n > n1 an a < ,


> 0 n2 ` : n > n2 an b < .

A n0 = max{n1 , n2 } , :
| a b |=| a an + an b || an a | + | an b |< 2 = 2

| a b|
=| a b |,
2

(). = b.
4.3.2 .
71

> 0 n0 ` : n > n0 an a < a < an < a + .

A M = max{a + , a1 , a2 ,..., an0 } , | an |< M , n ` , n

.
4.3.3 an a, an b ( a, b \ ) , :

lim n+ ( an bn ) = a b
lim n+ ( an bn ) = a b

lim n+ ( an /bn ) = a / b, b 0
. lim n + ( an bn ) = a b . :
an bn ab = an bn abn + abn ab = (an a )bn + a (bn b)
an a || bn + a || bn b < M + | a | .

O .
4.3.4 (i)

(ii)
(iii)
(iv)
(v)

A an a | an || a | .
A an a (a 0) ,
.
A an 0 bn anbn 0 .
A an a, bn b an < bn a b .
A an a, cn a an < bn < cn bn a ().

. (i) | an | | a | an a < .

|a|
|a|
|a|
a
< an < a
, n > n0 .
2
2
2
(iii) | an bn |< M .

(ii) an a <

= b+ a b .
2
2
2 2
(v) a < an bn cn < a + bn a < bn a .

(iv) a < an +

bn +

<b+

4.3.4 .
. n
. A = {an : n `}

, a = sup A. an a . > 0. - < , -


( . 1)

72

n0 ` : an0 > a . n an an0 n n0


an a . :

a < an0 < an a < a + | an a |< an a.


A n ,
M > 0 n0 : an0 > M , n > n0 an > M , lim n+ an = + .
2
.
( . 1)
.
, ( .. n = n2),
lim n + an , f(x)
n=x
f(x) x+.
4.3.5 (i) A n bn n>n0 bn + an + .

(ii) A |n| | bn| n>n0 bn 0 an 0 .


A. (i) , > 0 n1 ( ) ` : n > n1 bn > , n
bn n>n0,
> 0 n = max {n0 , n1} ` : n > n an bn > an + .

(ii) O.
4.3.6 (D Alembert)

(i) A lim n +

an +1
= > 1 an + .
an

(ii) A lim n +

an +1
= < 1 an 0 .
an

4.3.7 (Cauchy) (i) A lim n+ n | an | = < 1 an 0 .

(ii) A lim n+ n | an | = > 1 an + .


4.3.8 (Stolz) E an bn
lim n + bn = + , :

lim n+

an +1 an
a
= \ lim n+ n = \.
bn +1 bn
bn

73

0 0 < a <1

lim n+ a = 1,
a =1 .
+
a >1

f(x) = x (>0)
lim x + a x = 0, 0 < a < 1 , lim x + a x = +, a > 1.


lim n+ n k a n = 0, o
0 < a < 1.

f(x) =xk x (0<<1) (x>0), o (+) 0.


L Hospital k-:
lim x +

lim x +

xk
1

a

= lim x +

xk
1
, b = >1
x
b
a

kx k 1
k (k 1)(k 2)...1
= ... = lim x +
= 0.
x
b ln b
b x (ln b) k

lim n+ n a = 1, a > 0.
n

1
H bn = 1 + . :
n
lim n + bn = e .
n

a
: 1 + e a , n + .
n
4.4 Y- - Cauchy
O 4.4.1 : ` `,
, a ( n ) an .

a2 n , a2 n +1 , a3n , n = 1, 2,... an .
O 4.4.2 \ an
( (,+)) an .

74

:
() ,
() .
O 4.4.3 (. )
an an liman  lim sup an
(. liman  lim inf an ).


, :
lim an = liman = liman .

3
.
: H an = (1) n . :

a2 n = 1, n +
a2 n +1 = 1, n +

an = (1) n 1. :
liman =1 liman = 1 .

4.4.4 ( Cauchy) M an Cauchy

> 0 n0 N : n, m > n0 an am < .

:
4.4.1 ( Cauchy)

M an an Cauchy.
4 4.4.1

.
4.4.1 (Bolzano-Weierstrass) K
.
.

75

.
,
.
.

1. M :
lim n+

1
= 0, lim n+ n k = + .
k
n

. () > 0 n0 ( ) : n > n0

n > n0 ,

1
0 < . :
nk

1
1
1
= k < k.
k
n
n
n0

1
, :
n0k

1
1
1
n0k = n0 = k ,
k
n0

1
n0 n0 = k

( . 1), :
1
> 0 n0 = k

+ 1 , [.]

1
1
1
1

<
=
k
k
+ 1: n > n0 n k 0 < n k =

1
1
0
k
k + 1

(: [x] x < [x]+1),


1
lim n + k = 0 .
n
() > 0 n0 ( ) : n > n0 n k > . n > n0 , n k > n0k .

= n0k , :

= n0k n0 = k ,
n0 , n0 = k + 1 , :

76

) ( )
k

> 0 n0 = k + 1: n > n0 n k > n0k = k + 1 >

= ,

lim n+ n k = + .

2.

( )
n 2 +1

(a ) lim n+

e
n2
, () lim n+
n3
n2

( ) lim n +

n 3 2n 2 + 1
n +1
2n 1
, () lim n+
, () lim n+

2
4n 3n + 3
2n + 1
2n + 5

() lim n+

n n

3 3

n2

n2

1 + 2 + ... + n
, () lim n+ ( n n + 1)
n
x2
() f ( x) =
lim x + f ( x) = +
x 3
.
( ) lim n+

()

( ) 1 0, n + , (), ( e ) 0, n + .

e n
n2

n 2 +1

+1

n2

n2

() n = 3 k + , = 0,1,2. :

n n 3k + 3k +

= k + k + = k + k =

3 3
3
3
3
3
3
3 3
3 0,1/3, 2/3 .
() f ( x) =

x3 2 x 2 + 1
lim x + f ( x) = + .
4 x 2 3x + 3
x2

x +1
() f ( x) =
.
2x +1
x +1 1
lim x +
= , lim x + x 2 = + , :
2x +1 2
x2

x +1
1
lim x +
=
2x +1
2

77

=0.

x2

2x 1
() f ( x) =
.
2x + 5
2x 1
lim x +
= 1 , lim x + x 2 = + ,
2x + 5
1. :
x2

x
2x 1
lim x +
=
lim
e
x +

2x + 5

2 x 1
ln

2 x +5

=e

2 x 1 L ' Hosp .
lim x+ x 2 ln

2 x +5

= ... = e = 0 .

() /. Stolz: E
an = 1 + 2 + ... + n, bn = n . bn bn + ,
:

lim n+

an +1 an
a
1 + ... + n
n +1
= lim n+
= + lim n+ n = lim n+
= +
1
bn +1 bn
bn
n

() +-. (), (),(),().

3.

78

4.

5.

6.

79

7.

80

8. an =

. lim n+

an +1
= lim n+
an

n!
.
nn

(n + 1)!
(n + 1) n +1
= lim n+
n!
nn

1
1
1 +
n

1
< 1 an 0
e

D Alembert.


1. :
(a1 ) lim n+ 8 n 2 + 1 4 n + 1
(a2 ) lim n+ n a n + b n
(a3 ) lim n+
(a4 ) lim n+
(a5 ) lim n+

2n + (1) n
2n +1 + (1) n +1
(1) n n (n n )
n +1
n
ln n

1
(a6 ) lim n+ n
n
1+

1
(a7 ) lim n+ 1 +
n

1
n

5
(a8 ) lim n + n 5n + n n +1
n
n
5
(a9 ) lim n +
n
(a10 ) lim n+ ( 3 n / 5 )
(a11 ) lim n+ n(ln(n + 1) ln(n))
n

(a12 ) lim n+ 4 +
n

3
(a13 ) lim n + (1) n +
n
1 + 2 + ... + n
(a14 ) lim n+
n

81

2. :
() an a

a1 + ... + an
a, n + .
n

() () : an a n a1...an a, n + .

3. 2() :
lim n+

an +1
= n an .
an

: an =

n!
.
n

4. n :
2,

an +1 = 1
2
2 an + a
n

n =1
.

, n >1

an 2, n +

5. n :
n =1
1,

an +1 = 3an + 4
.
2a + 3 , n > 1
n
an 2.

6. an 2an an 1 + an +1 .
bn = an +1 an .

7. a2n a a2 n +1 a (
), an a.

82